Решение задачи оптимального выбора с групповым просмотром с помощью теоретико-игрового подхода - Доценко, С.И. (Кибернетика и вычислительная техника, 2015)
Рассмотрены три варианта игровой задачи выбора наилучшего элемента для случая, когда элементы разбиты на группы и за один шаг осуществляется одновременный просмотр элементов всей группы. Исходя из концепции сложного рационального поведения, для каждого из случаев найдены равновесные ситуации игры. Розглянуто три варіанти ігрової задачі оптимального вибору для випадку, коли об’єкти розбито на групи та за один крок здійснюється одночасний перегляд всіх елементів групи. Виходячи з концепції складної раціональної поведінки, для кожного з випадків знайдено ситуації рівноваги у грі. For the considered game the Bayes-Nash equilibrium is obtained for three different cases. Equilibrium points are shown at two-dimensional diagram. Depending on the problem statement, Nash equilibrium area may take different shapes — either single point (cases 1 and 2) or family of points inside the closed curve (case 3). In first two cases, the slight effect of anarchy is observed. Conclusion. The results confirm the general principle, that the game situation solutions, based on even trivial optimization problems, makes this solutions to be complicated. Based on the concept of a complex rational behavior for each of the cases found equilibrium situations of the game.